Efficacy of dodder vine extract as seed protectant against pulse beetle, Callosobruchus chinensis (Coleoptera: Bruchidae) - Rahman, MH; Ali, MA; Ahmed, KS (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted to find out the efficacy of dodder vine extract as seed protectant against pulse beetle, Callosobruchus chinensis on gram seed in the laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh during the period of February to May, 2009. The concentrations of dodder vine extract were 5, 2 and 1% respectively. Efficacies of these treatments were evaluated by considering oviposition, adult emergence, intensity of damage and seed weight loss done by pulse beetle. Dodder vine extract was found effective in checking oviposition, adult progeny development and severity of seed damage. Seeds treated with 5% concentration of dodder vine extract were less preferred for oviposition, adult emergence and seed weight loss by C. chinensis and this conc. might be useful in protection of pulse seed. Keywords: Dodder vine extract; Fecundity; Developmental performance; Seed weight loss; C. chinensis. DOI: 10.3329/jbau.v8i1.6395 J. Bangladesh Agril. Univ. 8(1): 35-38, 2010